(untitled) (The Journal of Psychology and Sociology, 2020)
The problem of personality factors that ensure the effectiveness of job performance is relevant in modern organizational psychology. The ‘Big Five’ is the most sought-after personality model. Despite the ambiguity in the interpretation of the names of individual scales, it continues to remain the most popular. The purpose of this article is to justify the advantages of using the ‘Big Five’ personality model based on a systematic approach. The scientific significance of applying a systematic approach is determined by the need to clarify the methodological apparatus of Kazakhstani psychology both in the field of scientific research and in the organization of university education. The methodology of the study is the systematic approach of V.A. Gansen, developed in the Lenin-grad (St. Petersburg) psychological school. The popularity of the theoretical model of the ‘Big Five’ in modern organizational psychology is explained by the fact that it describes a ‘Man’ as an integral system, and its Scales correspond in their description to the substructures of the ‘Man’ system: personality, subject of activity and individuality. The personality factor of job performance is primarily the ‘consciousness’ scale, the personality factor of effective learning and mastering new information for use in work is the ‘openness to experience’ scale which was empirically confirmed. Also, a logically correct correlation of the concepts of the ‘Big Two’, according to Eysenck, and the ‘Big Five’ was found. The systematic approach made it possible to understand the ‘Big Five’ as a reflection of the systemic nature of the human psyche, and could serve as a productive methodological basis for teaching organi-zational psychology at the university. Key words: ‘Big Five’ personality model, systemic approach, job performance.